Overactive bladder syndrome pharmacotherapy: future treatment options - Wróbel, Andrzej (Menopause Review/Przegląd Menopauzalny, 2015)
Overactive bladder syndrome (OAB) is a lifestyle disease and its incidence increases with age. Although it is not a life-threatening disease, it is known to have a significant impact on the quality of life. The first-choice pharmacological treatment of OAB is antimuscarinics. However, their limited clinical effectiveness and unsatisfactory tolerance profile, combined with the advancement of knowledge on the aetiopathogenesis of the disease, have inspired research on new pharmacotherapy options for OAB. Basic research has provided foundations for the development of new OAB treatments, which seem very promising and can be applied in clinical practice. The mechanisms of the studied compounds are based on their effect on certain receptors and neurotransmitters that contribute to regulating the micturition reflex. These compounds are not only more receptor-specific as compared to currently used drugs, but also some of them are organ-specific. Some of such compounds have already passed the proof-of-concept stage of development and have the therapeutic potential to determine the future of OAB pharmacotherapy. This review focuses on the mechanisms of substances that are now undergoing pre-clinical and clinical tests and their effects on the micturition cycle, while also identifying opportunities for using them with specific groups of patients. Due to the fact that OAB is a disease of symptoms and its aetiopathogenesis is complex, it seems that modern treatment methods should be tailor-made and based on the pathophysiological mechanisms that induce disease symptoms, rather than only treating the symptoms by inhibiting the contractility of the urinary bladder.